Inositol Hexakis Phosphate is the Seasonal Phosphorus Reservoir in the Deciduous Woody Plant Populus alba L. (27th July 2017) - Kurita, Yuko; Baba, Kei'ichi; Ohnishi, Miwa; Matsubara, Ryosuke; Kosuge, Keiko; Anegawa, Aya; Shichijo, Chizuko; Ishizaki, Kimitsune; Kaneko, Yasuko; Hayashi, Masahiko; Suzaki, Toshinobu; Fukaki, Hidehiro; et al.
Abstract: Seasonal recycling of nutrients is an important strategy for deciduous perennials. Deciduous perennials maintain and expand their nutrient pools by the autumn nutrient remobilization and the subsequent winter storage throughout their long life. Phosphorus (P), one of the most important elements in living organisms, is remobilized from senescing leaves during autumn in deciduous trees. However, it remains unknown how phosphate is stored over winter. Here we show that in poplar trees ( Populus alba L.), organic phosphates are accumulated in twigs from late summer to winter, and that IP6 (myo-inositol-1, 2, 3, 4, 5, 6-hexakis phosphate: phytic acid) is the primary storage form. IP6 was found in high concentrations in twigs during winter and quickly decreased in early spring. In parenchyma cells of winter twigs, P was associated with electron-dense structures, similar to globoids found in seeds of higher plants. Various other deciduous trees were also found to accumulate IP6 in twigs during winter. We conclude that IP6 is the primary storage form of P in poplar trees during winter, and that it may be a common strategy for seasonal P storage in deciduous woody plants.